Beyond International Commercial Arbitration? The Promise of International Commercial Mediation - S. I. Strong (Washington University Journal of Law & Policy, 2014)
International commercial arbitration has long been the preferred means of resolving complex business disputes in the cross-border context. However, the international corporate community has become somewhat disenchanted with that particular mechanism because of concerns about rising costs, delays, and procedural formality. As a result, parties are looking for other means of resolving international commercial disputes. One of the more popular alternatives is mediation. A question arises as to whether and to what extent international commercial mediation can serve as an adequate substitute for international commercial arbitration and, in particular, whether it can live up to the promise of delivering quick, inexpensive, and informal dispute resolution. To answer that question, this Article focuses on three separate issues. First, the discussion considers the unique characteristics of international commercial disputes to determine whether such matters are amenable to mediation. Second, the Article determines what incentives to use international commercial mediation might exist if savings of time, cost, and procedural formality are taken out of the equation. Third, the analysis describes how public international law might be used to support the development of international commercial mediation.
Keywords: international commercial arbitration; mediation; alternative dispute resolution; ADR; commercial arbitration; international mediation; international disputes; commercial disputes; international commercial mediation; benefits of international commercial mediation; enforcing international commercial mediation; dispute systems design theory; DSD theory